Perempuan: Sumber Dosa atau Sumber Hikmat? Tafsir Ulang Kejadian 3:1-24 dari Perspektif Feminis - Asnath Niwa Natar (Sekolah Tinggi Teologi Simpson, 2020)
There is an understanding that women and their bodies are the source of sin that must be shunned in our society. It is also evident in Christianity, where themes about women's bodies and their sexuality are also often associated with sin, transgression and punishment. This understanding is rooted in the story of Eve eating fruit in the Garden of Eden (Gen. 3:1-24) which is seen as a story of the